Assistance to the hospitalized child - Déa Silvia Moura da Cruz; Solange Fátima Geraldo da Costa; Maria Miriam Lima da Nóbrega (Rev Rene)
This is a study of bibliographical nature which aims to stimulate the reflexion of professionals who are involved in looking after hospitalized children. It takes into account the necessity of humanizing the assistance to such young patients. The study approaches aspects related to the psychosocial development of the child, their reactions towards hospitalization, highlighting the humanization of assistance as a strategy to be adopted on the minimization of the trauma resulted from hospitalization as well as the necessity to promote the continuous growth and development of the child during this period. Such reflections aim at a new behavior to be adopted by the multi-professional group towards the assistance to the hospitalized child.